Aspergillus niger as Tomato Fruit (Lycopersicum esculentum Mill.) Quality Enhancer and Plant Health Promoter - Anwer, Md Arshad; Khan, Mujeebur Rahman (Journal of Postharvest Technology, 2013)
In order to study the effects of Aspergillus niger, an experiment was carried  out with application of nursery root-dip treatment with A. niger isolate (10  g/100 seedlings for 10 minutes), found significantly (P ≤ 0.001) increased the  yield and dry matter content of tomato plants. Application of all sixteen  isolates of A. niger significantly increased the accumulation of salicylic acid,  total phenolic and chlorophyll contents of plant, and lycopene, ascorbic acid  (Vitamin C), Brix index, diameter of fruit skin, rate of pressure tolerance of  tomato fruit compared to untreated control. Among the all isolates, A. niger SkNAn5 found to be the most efficient with increasing 54% yield and 59.8%  dry matter of tomato plants. A. niger SkNAn5 also maximum significantly  increased the salicylic acid of root, shoot with improved fruit quality of tomato  having increased amount of vitamin C (35.59 g/100 g against control 23.9  g/100 g), lycopene (9.8 mg/100 g against control 8.3 mg/100 g), and also had  increased rate of pressure tolerance of fruits (2.84 kg/cm against control 1.35  kg/cm). Increase in salicylic acid concentration may also increased the  diameter of fruit skin with most efficient isolate SkNAn5 (0.49 mm) almost  two fold compared to control (0.26 mm). Fruit Brix index of tomato plants  treated with SkNAn5 significantly increased (8.75) compared to non-treated  plants (5.81). These results suggest that nursery application of A. niger SkNAn5 may improve quantity and quality of tomato fruits.  `
Keywords: Tomato; Aspergillus niger; Quality; Ascorbic acid; Lycopene; Salicylic acid